2007
DOI: 10.1161/01.hyp.0000251301.12357.ba
|View full text |Cite
|
Sign up to set email alerts
|

Inositol Phosphoglycan P-Type in Preeclampsia

Abstract: Abstract-A state of insulin resistance has been demonstrated in active preeclampsia, and women with clinical evidence of insulin resistance are at higher risk to develop this syndrome during pregnancy. Recently, inositol phosphoglycan P-type, a putative second messenger of insulin action, has been implicated in the pathophysiology of preeclampsia and is increased in the placenta, amniotic fluid, and maternal urine of preeclamptic women compared with normal pregnant women. We report here a case-control study to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 32 publications
1
33
0
1
Order By: Relevance
“…Second, and this a point where we want to create a debate, for 15 years now (Kunjara et al, 2000;Williams et al, 2007;Scioscia et al, 2014), there has been evidence that the detection of the presence of inositol -phosphoglycans type P (IPG-P) in pregnant women's urine is strongly specific to preeclampsia, and correlates absolutely with proteinuria. However, IPG-P appears 2-7 weeks before the onset of clinical disease.…”
Section: Vascular (Maternal Disease In the Third Trimester Of Pregnancy)mentioning
confidence: 99%
See 1 more Smart Citation
“…Second, and this a point where we want to create a debate, for 15 years now (Kunjara et al, 2000;Williams et al, 2007;Scioscia et al, 2014), there has been evidence that the detection of the presence of inositol -phosphoglycans type P (IPG-P) in pregnant women's urine is strongly specific to preeclampsia, and correlates absolutely with proteinuria. However, IPG-P appears 2-7 weeks before the onset of clinical disease.…”
Section: Vascular (Maternal Disease In the Third Trimester Of Pregnancy)mentioning
confidence: 99%
“…• Role of hyperglycosylated HCG (deepness of implantation) (Cole et al, 2008) • Immunological animal model for PE (Ahmed, Girardi et al, workshop 2008, published 2010 • Pivotal role of Treg cells (≈2010s) (Clark and Chaouat, 2012) Rademacher, London University) to the discovery of IPG-P (Kunjara et al, 2000;Williams et al, 2007;Scioscia et al, 2014). Finally, and to come back to pravastatin, current trials are ongoing in areas with predominant LOP.…”
Section: Major Advances In the Immunology Of Reproductionmentioning
confidence: 99%
“…[93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111] Recent studies have indicated a relationship between elements of the metabolic syndrome such as elevated serum triglycerides and free fatty acids, insulin resistance, and glucose intolerance and the occurrence of preeclampsia. [93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111] In fact, several authors have suggested insulin resistance may presage the manifestation of preeclampsia, 98 -105 whereas Thadhani et al have proposed that insulin resistance during pregnancy may interact with other conditions such as impaired angiogenesis to generate a preeclamptic phenotype. 101 Although plasma levels of lipids are increased during normal pregnancy, plasma concentrations of both triglyceride-rich lipoproteins and nonesterified fatty acids are significantly increased in women that develop preeclampsia relative to normal pregnant women.…”
Section: Metabolic and Dietary Factorsmentioning
confidence: 99%
“…Ces facteurs antiangiogéniques circulants pourraient s'intégrer au modèle proposé en 1993 par David Haig (Harvard, États-Unis) de conflit génétique maternofoetal [48] comme le reflet d'une stratégie de sauvetage foetal. De même, les inositol phosphoglycans-P [IPG-P] (présentés dans différents colloques par Rademacher, Londres, GB, et Scioscia, Vérone, Italie) pourraient représenter l'équivalent métabolique d'un signal de détresse foetal et participer à l'inflammation endothéliale [49]. La preuve définitive de l'implication de ces médiateurs bioactifs laisse espérer la mise au point de thérapeutiques du syndrome maternel dans un futur très proche (moins d'une décennie).…”
Section: Débats Sur L'activation Cellulaire Endothéliale Généralisée unclassified